Inhibition of ammonia and hydrogen sulphide as faecal sludge odour control in dry sanitation toilet facilities using plant waste materials - Bernice Mawumenyo Senanu (Nature Portfolio, 2021)
Abstract On-site dry sanitation facilities, although cheaper than wet sanitation systems, suffer from high malodour and insect nuisance as well as poor aesthetics. The high odour deters users from utilizing dry sanitation toilets as an improved facility leading to over 20% open defecation in Sub-Saharan Africa. To address this malodour concern, this study first assessed odour levels, using hydrogen sulphide (H2S) and ammonia (NH3) as indicators, on two dry sanitation facilities named T1 and T2. The potential of using biomass (sawdust, rice husk, moringa leaves, neem seeds), ash (coconut husk, cocoa husk) or biochar (sawdust, rice husk, bamboo) as biocovers to remove or suppress odour from fresh faecal sludge (FS) over a 12-day period was investigated. Results showed that the odour levels for H2S in both T1 (3.17 ppm) and T2 (0.22 ppm) were above the threshold limit of 0.05 ppm, for unpleasantness in humans and vice versa for NH3 odour levels (T1 = 6.88 ppm; T2 = 3.16 ppm; threshold limit = 30 ppm limit). The biomasses exhibited low pH (acidic = 5–7) whereas the biochars and ashes had higher pHs (basic = 8–13). Basic biocovers were more effective at H2S emission reduction (80.9% to 96.2%) than acidic biocovers. The effect of pH on suppression of NH3 was determined to be statistically insignificant at 95% confidence limit. In terms of H2S and NH3 removal, sawdust biochar was the most effective biocover with odour abatement values of 96.2% and 74.7%, respectively. The results suggest that biochar produced from locally available waste plant-based materials, like sawdust, can serve as a cost-effective and sustainable way to effectively combat odour-related issues associated with dry sanitation facilities to help stop open defecation.